South American indigenous weapons aboard the San Pedro shipwreck of 1596 - Ostapkowicz, J; Brock, F; Wiedenhoeft, AC; Bray, W (National Museum of Bermuda Press, 2023)
In 1596, the San Pedro, en route from Colombia to Spain, went down in a hurricane off Bermuda, with the loss of its entire cargo. Among the ship’s contents, salvaged between 1950 and 1961, was the most complete collection of 16th century Indigenous weapons recovered from a maritime context, including bows and arrows, darts, stone axes, and two examples of a rare, distinctive style of club. These clubs, featuring a flaring terminal end embellished with recessed two-dimensional geometric design panels, are documented in 16th and 17th century accounts of Indigenous warriors in the Lesser Antilles and northeastern South America. Other examples entered European collections as exotica from the “New World,” eventually becoming part of the earliest museums in the 17th century; only a small corpus of approximately 80 examples survives today. This paper recontextualises the clubs recovered from the San Pedro, documenting their recovery, and providing a chronological and cultural framework through radiocarbon dating, wood identification and a comparison to other clubs of this style.